2018
DOI: 10.1038/s41467-018-03671-5
|View full text |Cite
|
Sign up to set email alerts
|

Valence and spin states of iron are invisible in Earth’s lower mantle

Abstract: Heterogeneity in Earth’s mantle is a record of chemical and dynamic processes over Earth’s history. The geophysical signatures of heterogeneity can only be interpreted with quantitative constraints on effects of major elements such as iron on physical properties including density, compressibility, and electrical conductivity. However, deconvolution of the effects of multiple valence and spin states of iron in bridgmanite (Bdg), the most abundant mineral in the lower mantle, has been challenging. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 71 publications
(146 reference statements)
5
47
0
Order By: Relevance
“…Hummer and Fei (2012) investigated Fe 3+ substitution mechanisms using multianvil experiments; however, their experiments did not reach chemical equilibrium as demonstrated by the coexistence of unreacted MgO and SiO 2 phases. Essentially, previous studies (Andrault & Bolfan-Casanova, 2001;Catalli et al, 2010;Hummer & Fei, 2012;Liu et al, 2018;Sinmyo et al, 2019) used starting materials without saturation of MgO (atomic Mg/Si = 1.0 or lower), which may prohibit the formation of MgFeO 2.5 based on observations that MgAlO 2.5 decreases with decreasing Mg/Si ratio in the MgO-SiO 2 -Al 2 O 3 system because of the reaction 2MgO + Al 2 O 3 = 2MgAlO 2.5 (Liu, Nishi, et al, 2017). In contrast, the Earth's lower mantle contains ferropericlase, and the concentration of MgFeO 2.5 should thus be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…Hummer and Fei (2012) investigated Fe 3+ substitution mechanisms using multianvil experiments; however, their experiments did not reach chemical equilibrium as demonstrated by the coexistence of unreacted MgO and SiO 2 phases. Essentially, previous studies (Andrault & Bolfan-Casanova, 2001;Catalli et al, 2010;Hummer & Fei, 2012;Liu et al, 2018;Sinmyo et al, 2019) used starting materials without saturation of MgO (atomic Mg/Si = 1.0 or lower), which may prohibit the formation of MgFeO 2.5 based on observations that MgAlO 2.5 decreases with decreasing Mg/Si ratio in the MgO-SiO 2 -Al 2 O 3 system because of the reaction 2MgO + Al 2 O 3 = 2MgAlO 2.5 (Liu, Nishi, et al, 2017). In contrast, the Earth's lower mantle contains ferropericlase, and the concentration of MgFeO 2.5 should thus be maximized.…”
Section: Introductionmentioning
confidence: 99%
“…A noticeable volume collapse of 0.5(±0.1)% has been observed across the spin transition between 18 and 25 GPa from P-V data at 300 K (1) O 3 (Bgm5) as a function of pressure at 300 K. Solid circles are experimental data from two runs, where the cell was loaded with neon in the first run (Run 1, green circles) and loaded with helium in the second run (Run 2, red circles), and blue circles are results from Run 2 during decompression. Data from Run 2 in He medium were used in the thermoelastic modeling (Run 1 data were not used because of suspected nonhydrostaticity at higher pressures; see supporting information for details (Liu et al, 2018). Data from Run 2 in He medium were used in the thermoelastic modeling (Run 1 data were not used because of suspected nonhydrostaticity at higher pressures; see supporting information for details (Liu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Geophysical Research Letters in bridgmanite with composition (Mg 0.9 Fe 0.1 )SiO 3 containing 20% Fe 3+ (Mao et al, 2015), and recent experimental study observed 1.9% volume decrease within the spin transition of B-site Fe 3+ in ferric-iron-only bridgmanite (Mg 0.46 Fe 3+ 0.53 )(Fe 3+ 0.51 Si 0.49 )O 3 (Liu et al, 2018). In contrast, both Fe 3+ and Fe 2+ in the A site have been reported to remain in the HS state throughout the entire lower-mantle pressure range (24-130 GPa) (Dorfman et al, 2015;Hsu et al, 2010Hsu et al, , 2011Lin et al, 2016).…”
Section: 1029/2018gl077764mentioning
confidence: 94%
See 2 more Smart Citations